Experiences of harassment and empowerment after sharing personal abortion stories publicly - Katie Woodruff; Rosalyn Schroeder; Stephanie Herold; Sarah C.M. Roberts; Nancy F. Berglas (Elsevier, 2020)
Objective: In recent years, in an attempt to counter stigma and increase empathy, public education campaigns have encouraged people to share their personal abortion stories. This exploratory study sought to document negative and positive experiences of those who have shared their abortion stories publicly. Study design: We conducted an anonymous online survey of people who have shared their abortion story publicly (N = 88), recruited via partners affiliated with two abortion story-sharing campaigns. The survey asked about the context in which respondents shared their abortion story, any negative and positive experiences online and in "real life" as a result of story sharing, and any problems or benefits resulting from these experiences. We analyzed survey data using descriptive statistics, bivariate analyses and categorizing responses to open-ended questions. Results: Sixty percent of respondents reported experiencing harassment and other negative incidents after sharing their story publicly. These experiences contributed to emotional stress, problems with loved ones and difficulties at work and/or school. These harms were reported even by many respondents who used only a first name or alias when sharing their story. Despite this, positive experiences as a result of story sharing were reported by four out of five respondents and motivated many to continue sharing their story. Conclusions: This exploratory study indicates that many people who share their abortion story publicly find it to be an empowering, rewarding experience. Yet they also experience harassment and threats at high rates. Future research should explore both positive and negative experiences in more depth. Implications: Sharing one's personal abortion story as part of a public education campaign can be a positive, empowering experience. Nevertheless, policymakers, journalists and reproductive health advocates should recognize the potential harms experienced by people who share their abortion story publicly and consider measures to support these individuals.